The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/13880200701741120
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,2,3,4-Tetrahydroeudistomin U Derivatives and PreliminaryIn Vitro. Antitumor Evaluation

Abstract: A series of novel 2-substituted 1,2,3,4-tetrahydroeudistomin U derivatives were synthesized by the key PictetSpengler cyclization reaction and their in vitro antitumor activities were evaluated using Pyricularia oryzae Cavara and Caco-2 cancer cells. Most of the 2-alkyl-1,2,3,4-tetrahydroeudistomin U compounds (19-23) showed potent inhibitory activities in both of the biological tests. Preliminary structure-activity relationships are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Under MW agitation at 100 ο C, the reaction time could be decreased from 4 h to 30 min ( Table 2). The synthesis of 9a has already been achieved [22][23][24] from 1H-indole-3-ethanamine and 1Hindole-3-carboxaldehyde via Pictet-Spengler condensation. The main advantage of our method is the application of indole instead of indole-3-carboxaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…Under MW agitation at 100 ο C, the reaction time could be decreased from 4 h to 30 min ( Table 2). The synthesis of 9a has already been achieved [22][23][24] from 1H-indole-3-ethanamine and 1Hindole-3-carboxaldehyde via Pictet-Spengler condensation. The main advantage of our method is the application of indole instead of indole-3-carboxaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…, when 6,7-dihydrothieno[3,2-c]pyridine (85) was reacted either with 20a or with 79. From the results inTable 15(entries 8-11), it can be concluded that 85 has a higher reactivity with indolederivatives as compared with 4,6-dihydro-3H-benz[c]azepine(84).…”
mentioning
confidence: 99%
“…When the reaction was repeated under MW agitation at 100 ο C, the reaction time could be decreased from 4 h to 30 min(Table 16). The synthesis of 93a was earlier achieved[82][83][84] from 1H-indole-3-ethanamine and 1H-indole-3-carboxaldehyde via Pictet-Spengler condensation. The main advantage of our method is the application of indole derivatives instead of indole-3-carboxaldehyde, the direct α-arylation of partially saturated β-carbolines with electronrich aromatic compounds opening up new areas of diversity for this reaction.…”
mentioning
confidence: 99%